2021
DOI: 10.3390/cells10071623
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Cilia in Different Mouse Tissues

Abstract: Cilia are microtubule-based hair-like organelles that extend from the cell surface. However, the existence and distribution of cilia in each organ and tissue at the postnatal stage in vivo remain largely unknown. In this study, we defined cilia distribution and arrangement and measured the ciliary lengths and the percentage of ciliated cells in different organs and tissues in vivo by using cilium dual reporter-expressing transgenic mice. Cilia were identified by the presence of ARL13B with an mCherry+ signal, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 50 publications
(62 reference statements)
5
9
0
Order By: Relevance
“…Leftward-directed fluid flow, which is produced in embryonic node cilium movement, was regarded as essential for left-right axis determination in mice. Consistently, in our previous study [ 58 ], about 2% of cilia with the irregular movement were identified in mouse NP. However, the cilium movement type is different from the clockwise movement of cilia in embryonic notochord/node cells [ 59 ].…”
Section: Primary Cilia and Ciliary Proteins In Skeletal Diseasessupporting
confidence: 90%
See 1 more Smart Citation
“…Leftward-directed fluid flow, which is produced in embryonic node cilium movement, was regarded as essential for left-right axis determination in mice. Consistently, in our previous study [ 58 ], about 2% of cilia with the irregular movement were identified in mouse NP. However, the cilium movement type is different from the clockwise movement of cilia in embryonic notochord/node cells [ 59 ].…”
Section: Primary Cilia and Ciliary Proteins In Skeletal Diseasessupporting
confidence: 90%
“…Recently, we carefully reported that primary cilia are present in the mouse IVD with the cilia-GFP and ARL13B-mCherry;Centrin2-GFP cilium dual reporter-expressing transgenic mouse model [ 57 , 58 ]. With these two mouse models, we found that the primary cilium length was 0.5-15 μ m in the NP and 0.5-3.5 μ m in the AF.…”
Section: Primary Cilia and Ciliary Proteins In Skeletal Diseasesmentioning
confidence: 99%
“…The isolated chondrocytes were treated with SAG for 24 h, and then ciliogenesis was analyzed by immunofluorescence staining of Arl13b (a primary cilia marker). 23 The results showed that cilia were present in all groups ( Figure 3 A). Quantitative analysis showed no significant differences in cilia number, length, or orientation among the wild-type, Ihh-deficient, and Ihh-deficient SAG treatment groups either in vivo or in vitro ( Figure 3 B; Figures S4 A and S4B).…”
Section: Resultsmentioning
confidence: 87%
“…Primary cilia are displayed on fibroblasts in the heart, Ref. [55] as well as on vascular endothelial cells, though expression on valvular endothelium decreases over time, from abundance in embryologic samples to near absence in adult samples [13,56,57]. Most cardiac interstitial (mesenchymal) cells also display primary cilia [57].…”
Section: Primary Cilia Locationsmentioning
confidence: 99%
“…Primary cilia have been the focus of research since the 1960s, when they were first recognized as distinct from motile cilia and present in most mammalian tissues [10,11]. Diseases related to cilia gene mutations, coined ciliopathies, have since been identified in many organ systems [12,13]. Cilia's role in the cardiovascular system has been more recently defined, with large studies and reviews describing the occurrence of most, if not all, congenital heart diseases in response to mutations in cilia-related genes [14,15].…”
Section: Introductionmentioning
confidence: 99%